2022
DOI: 10.3390/rs14081875
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Mapping of Paddy Rice Extent and Growth Stages across Peninsular Malaysia Using a Fusion of Sentinel-1 and 2 Time Series Data in Google Earth Engine

Abstract: Rice is the staple crop for more than half the world’s population, but there is a lack of high-resolution maps outlining rice areas and their growth stages. Most remote sensing studies map the rice extent; however, in tropical regions, rice is grown throughout the year with variable planting dates and cropping frequency. Thus, mapping rice growth stages is more useful than mapping only the extent. This study addressed this challenge by developing a phenology-based method. The hypothesis was that the unsupervis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 75 publications
0
18
0
Order By: Relevance
“…For instance, a study conducted by Fatchurrachman, Rudiyanto et. al., (2022) 25 exemplifies the utility of combining Sentinel-1 and Sentinel-2 data for rice paddy mapping in the Mekong Delta. They employed SAR backscatter data from Sentinel-1 to capture rice field inundation dynamics, while Sentinel-2's multispectral imagery was used to discern crop growth stages and land cover variations.…”
Section: Combine Sentinel-1 and 2 For Rice Paddy Mappingmentioning
confidence: 95%
“…For instance, a study conducted by Fatchurrachman, Rudiyanto et. al., (2022) 25 exemplifies the utility of combining Sentinel-1 and Sentinel-2 data for rice paddy mapping in the Mekong Delta. They employed SAR backscatter data from Sentinel-1 to capture rice field inundation dynamics, while Sentinel-2's multispectral imagery was used to discern crop growth stages and land cover variations.…”
Section: Combine Sentinel-1 and 2 For Rice Paddy Mappingmentioning
confidence: 95%
“…Sentinel-1 data used in this study were invoked on the GEE platform by the 'COPER-NICUS/S1_GRD' dataset (synthetic aperture radar GRD product), also with a planting year as the time range, totaling 33 images. The dual-polarized VH band in interference Wide width (IW) mode was chosen because it is more sensitive to rice backscattering than VV [32,40]. The detailed data used by the research are shown in Table 1, and the distribution of the number of effective Sentinel data observations in the rotation cycle of the study area is shown in Figure 3.…”
Section: Remote Sensing Datamentioning
confidence: 99%
“…This approach yielded improvements of 5.82% and 2.39% in accuracy compared to the use of Sentinel-1 or Sentinel-2 time series data alone, respectively [29]. Fatchurrachman et al [32] Synthesized the time series dataset of Sentinel-1 VH polarization and Sentinel-2 NDVI month by month, and conducted unsupervised classification of rice by k-means clustering. The overall accuracy and Kappa coefficient of rice extraction were 95.95% and 0.92.…”
Section: Introductionmentioning
confidence: 99%
“…Google Earth Engine (GEE), a cloud-based geospatial analysis platform, can effectively perform large-scale and long-time processing of satellite imagery to detect environmental change patterns [21]. Therefore, GEE has been widely applied to analyze land use changes [22,23], identify crop types and boundaries [24,25], evaluate ecosystem services responses to biotic and abiotic disturbances [26,27] and monitor environmental quality and integrity [28].…”
Section: Introductionmentioning
confidence: 99%